Development of a Quality Manual for ActivAsia, Inc. - Buera, Christian Arnold A.
With the ever-increasing demand for more quality goods and services in a highly competitive global business environment, it is imperative for firms to be able to inject an organizational culture for excellence and emphasis on quality results. Laying down the foundation for a quality system is something that could spell survival for firms who are entrusted with managing marketing and promotion initiatives for clients with multi-million dollar market shares. This study focuses on the development of a formal quality manual for ActivAsia, Inc., an integrated channel activation marketing agency, providing high-level expertise to leading fast-moving consumer goods (FMCG) and retail companies in various channels. It is also the objective of this study to utilize the quality manual developed in this study as a basis for the formulation and implementation of a formal quality management system for ActivAsia, Inc. The Philippine National Standard, PNS ISO 9001 : 2008, Quality management systems-Requirements, which is the same as the International Standard ISO 9001 : 2008, was used as a framework for the development of the quality manual. Upon completion of the study, the quality manual should also serve as a master plan in the planning and crafting of the necessary documentation required for ActivAsia, Inc., and its plans for future ISO certification.